Nuclear operators and its applications "Les opérateurs nucléaires et leurs applications" - ASMA HAMMOU (University of M'Sila, 2024)
In the present study, our primary main is extend operator ideal theory to multilinear operators and polynomials. In this context, we direct our attention towards the study of two distinct concepts to p-nuclear operators. The first study involves an extension of the notion of weakly p-nuclear operators, which was introduced by J.M. Kim, in (J. Korean Math. Soc 56 (2019), 225-237), to encompass multilinear operators and polynomials. We show that this class forms a Banach multi-ideal (respectively, polynomials), In the quest to look for a class of operators that represent bounded linear functionals on the space of weakly p-nuclear multilinear operators (respectively, polynomials) led us to the introduction of the class of quasi Cohen p-nuclear multilinear operators (respectively, polynomials). We show that such operators realise a Pietsch domination theorem. Moreover, we prove that, under the usual conditions, there exists an isometric isomorphism between the dual of the space of weakly p-nuclear multilinear operators (respectively, polynomials) and the space of quasi Cohen p- nuclear multilinear operators (respectively, polynomials). The second study is the extension of the concept of Cohen p-nuclear operators introduced by J. S. Cohen in (Math. Ann. 201(1973) 177-201) to polynomials between Banach lattices, we show that a polynomial is positive Cohen p-nuclear if, and only if, its associated symmetric multilinear operator is positive Cohen p-nuclear. Additionally, the study defines positive Cohen p-nuclear polynomials as a combination of positive Cohen strongly p-summing polynomials and positive absolutely p-summing linear operators, and shedding light on their relationship with other classes.
Dans l’étude actuelle, notre objectif principal est d’étendre la théorie des opérateurs idéaux aux opérateurs multilinéaires et aux polynômes. Dans ce contexte, nous concentrons notre attention sur l’étude de deux concepts distincts concernant les opérateurs p- nucléaires. La première étude concerne une extension de la notion d’opérateurs faiblement p-nucléaires, introduite par J. M. Kim, afin d’inclure les opérateurs multilinéaires et les polynômes. Nous montrons que cette classe forme un multi-idéal de Banach (respectivement, les polynômes). Dans notre quête pour trouver une classe d’opérateurs représentant des fonctionnelles linéaires bornées dans l’espace des opérateurs multilinéaires faiblement p-nucléaires (respectivement, les polynômes), nous avons introduit la classe des opérateurs multilinéaires quasi Cohen p-nucléaires (respectivement, les polynômes). Nous montrons que de tels opérateurs satisfont un théorème de domination de Pietsch. De plus, nous prouvons que, dans les conditions habituelles, il existe un isomorphisme isométrique entre le dual de l’espace des opérateurs multilinéaires faiblement p-nucléaires (respectivement, les polynômes) et l’espace des opérateurs multilinéaires quasi Cohen p-nucléaires (respectivement, les polynômes). La deuxième étude concerne l’extension du concept d’opérateurs Cohen p-nucléaires introduit par Cohen aux polynômes entre les espaces de Banach réticulés. Nous montrons qu’un polynôme est positif Cohen p-nucléaire si et seulement si son opérateur multilinéaire symétrique associé est positif Cohen p-nucléaire. De plus, cette étude définit les polynômes positifs Cohen p-nucléaires comme une combinaison de polynômes positif Cohen fortement p-sommant et d’opérateurs linéaires positif absolument p-sommant, mettant en lumière leur relation avec d’autres classes.
Keywords: Weakly p-nuclear; Quasi Cohen p-nuclear; Banach lattice; Positive p-summing; Positive Cohen strongly p-summing; Positive Cohen p-nuclear; Pietsch domination theorem.